2017
DOI: 10.1016/j.amsu.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

New method of indocyanine green fluorescence sentinel node mapping for early gastric cancer

Abstract: BackgroundThe present study describes the retrospective feasibility study of ICG fluorescence SN mapping in back-table for early gastric cancer using PINPOINT®.MethodSN mapping were performed as following; the day before surgery, 0.5 ml ICG was injected endoscopically in four quadrants of the submucosa surrounding the gastric cancer using an endoscopic puncture. Intraoperatively, the gastrocolic ligament was divided to visualize all possible directions of lymphatic flow from the stomach. PINPOINT® (NOVADAQ, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Subserosal injection seems to be beneficial given that the surgeon can control the injection by her/himself. 21,[23][24][25][26][27]30,31 Additionally, in my personal opinion, ICG injected into the subserosal layer reaches to the lymphatic pathway more quickly compared with ICG injected into the submucosal layer. However, the location of the primary tumor is frequently difficult to identify using the external view unless the tumor is too advanced to be easily visualized.…”
Section: Injection Of Icg Into the Stomachmentioning
confidence: 84%
See 2 more Smart Citations
“…Subserosal injection seems to be beneficial given that the surgeon can control the injection by her/himself. 21,[23][24][25][26][27]30,31 Additionally, in my personal opinion, ICG injected into the subserosal layer reaches to the lymphatic pathway more quickly compared with ICG injected into the submucosal layer. However, the location of the primary tumor is frequently difficult to identify using the external view unless the tumor is too advanced to be easily visualized.…”
Section: Injection Of Icg Into the Stomachmentioning
confidence: 84%
“…29 Both systems provide fused images from white light and NIR imaging. 30 Other companies have reported prototypes of laparoscopic systems from other companies, 31 and several laparoscopic systems, including the D-light TM system (Karl-Storz, Tuttlingen, Germany), AIM ENV TM system (Stryker, San Jose, CA, USA), and IR TM system (Olympus, Tokyo, Japan), are currently available in the market (Fig. 1).…”
Section: Icg and Nir Fluorescent Optical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting method which demonstrated the utility of indocyanine green injection in early gastric cancer patients was described by Hironori Ohdaira et al in 2017; the authors proposed preoperative injection of indocyanine green via endoscopy in the four quadrants of the submucosal area, one day before surgery; at the time of surgery the Pinpoint system was used in order to illuminate the region and detect the sentinel lymph nodes after dissecting the gastrocolic ligament. By using this method, the authors reported a successful identification of the sentinel lymph node in six cases; one case presenting a positive lymph node for indocyanine green staining was finally proved to have metastatic deposits 20 .…”
Section: Sentinel Lymph Node Biopsy In Gastric Cancer Patientsmentioning
confidence: 99%
“…In recent years, near-infrared (NIR) imaging with indocyanine green (ICG) has been developed for the visualization of sentinel lymph nodes and real-time guidance of lymph nodes dissection in various cancers [6][7][8][9] . Due to the ne tissue penetration of signal, ICG-mediated NIR uorescent imaging has become a promising technique in navigational laparoscopic surgery 10,11 .…”
Section: Introductionmentioning
confidence: 99%